Work in Thermodyanamics - Ahmad, Jamil; A.A. Ddamba, Wilfred (Asian Journal of Chemistry, 2010)
The expression for mechanical work obtained in the expansion of a gas commonly used in physical chemistry textbooks is critically examined. The mathematical form of the first law of thermodynamics is arrived at by a procedure that is consistent with the common definition of mechanical work. The treatment is extended to explain the concept of reversible and irreversible work.